BS ISO/IEC 14543-5-103. Information technology. Home Electronic System (HES) architecture. Part 5-103. Intelligent grouping and resource sharing for HES Class 2 and Class 3. RA smart audio interconnection profile (8th July 2021) - British Standards Institution,
No abstract available